Ceramic material for internal support of vacuum furnace and preparation method thereof
By adopting specific ceramic materials and preparation processes, the problems of damage to the furnace tube and short life due to the installation method of the existing quartz furnace tube are solved, and the low expansion, high strength and high temperature resistance of the ceramic material are achieved, extending the service life of the vacuum furnace and maintaining a clean environment.
Patent Information
- Application Number
- CN202411948920.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The existing internal components of the quartz furnace tube, including welding hooks and removable hooks, will cause damage to the furnace tubes, and will have a short lifespan, making it difficult to meet the long-term use requirements of high-temperature environments.
A ceramic material, including quartz sand, aluminum hydroxide, magnesium silicate, borax, lithium carbonate, titanium dioxide, cerium oxide, sodium carbonate and sodium nitrate, is prepared by high temperature melting, casting forming and annealing, combined with mechanical treatment and heat treatment, ceramic materials for the internal bracket of the vacuum furnace are prepared.
The ceramic material has a low coefficient of expansion, high bending strength and temperature resistance, and can be used in high-temperature environments for a long time. Its thermal conductivity is similar to that of the quartz furnace tube, avoids stress concentration, extends the service life of the vacuum furnace, and maintains the cleanliness of the vacuum environment.
Smart Images

Figure CN119751099A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials and relates to a ceramic material, in particular to a ceramic material for an internal bracket of a vacuum furnace and a preparation method thereof. Background Art
[0002] Quartz furnace tubes are core consumables required in the semiconductor industry and raw material processing. For example, they are widely used in diffusion, oxidation, annealing and other steps in the wafer manufacturing process. The main functions of quartz furnace tubes include two aspects. One is to provide a high-temperature resistant vacuum environment for the wafer, and the other is to provide a bracket for the installation of some components inside the vacuum environment.
[0003] Regarding the installation of components inside the quartz furnace tube. There are currently two mainstream methods in the market. One is the welding hook, which uses a quartz welding rod to directly weld a quartz hook on the inner wall of the quartz tube to carry related components; the other is a detachable hook, which uses metal materials to prepare some detachable hook brackets, which are placed inside the quartz tube to support the components. Among them, the welding hook has the following disadvantages: 1) The welding hook will damage the furnace tube itself and affect the safe use of the quartz tube; 2) The construction of the welding hook is difficult, and the subsequent processes will involve surface treatment, secondary annealing and other processes; 3) The welding hook is easily damaged and cannot be repaired. When it is damaged too much and cannot meet the use requirements, the quartz furnace tube needs to be replaced. The detachable hook has the following disadvantages: 1) The detachable hook is made of metal material and cannot be used in a high temperature environment for a long time, and its life is short; 2) The thermal conductivity of the metal detachable hook is too different from that of the quartz glass, which will form stress concentration at the contact point, thereby reducing the life of the quartz tube; 3) The metal detachable hook is easily oxidized, generating a pollution source, affecting the cleanliness of the vacuum environment.
[0004] In summary, the welded hooks and detachable hooks currently available in the market will have an adverse effect on the life of the quartz furnace tube. Therefore, it is necessary to provide a hook made of non-metallic materials to avoid the above disadvantages. Summary of the invention
[0005] The purpose of the present invention is to provide a ceramic material for a bracket inside a vacuum furnace and a preparation method thereof. The bracket prepared with the ceramic material provided by the present invention is used inside a vacuum furnace, which can effectively increase the life of the vacuum furnace, avoid the internal bracket from causing damage to the vacuum furnace during installation or use, and also increase the service life of the internal bracket.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In the first aspect, the present invention provides a ceramic material for an internal support of a vacuum furnace. The raw materials for preparing the ceramic material include, in terms of mass fraction: 25-40wt% quartz sand, 20-30wt% aluminum hydroxide, 12-20wt% magnesium silicate, 6-12wt% borax, 2-5wt% lithium carbonate, 2-8wt% titanium dioxide, 1-2wt% cerium oxide, 1-5wt% sodium carbonate and 0.2-1.0wt% sodium nitrate.
[0008] Exemplarily, the content of the quartz sand in the raw material for preparing the ceramic material for the internal bracket of the vacuum furnace is 25-40wt%, for example, it can be 25wt%, 28wt%, 31wt%, 34wt%, 37wt% or 40wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0009] The content of the aluminum hydroxide is 20-30wt%, for example, it can be 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt% or 29wt% or 30wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0010] The content of magnesium silicate is 12-20wt%, for example, 12wt%, 14wt%, 16wt%, 18wt% or 20wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0011] The content of borax is 6-12wt%, for example, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt% or 12wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0012] The content of the lithium carbonate is 2-5wt%, for example, 2wt%, 3wt%, 4wt% or 5wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0013] The content of the titanium dioxide is 2-8wt%, for example, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt% or 8wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0014] The content of cerium oxide is 1-2wt%, for example, 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0015] The content of sodium carbonate is 1-5wt%, for example, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0016] The content of sodium nitrate is 0.2-1.0wt%, for example, it can be 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% or 1.0wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0017] As a preferred technical solution of the present invention, the raw materials for preparing the ceramic material include, in terms of mass fraction percentage: 30-35wt% quartz sand, 20-25wt% aluminum hydroxide, 15-18wt% magnesium silicate, 8-10wt% borax, 3.5-4.5wt% lithium carbonate, 4-6wt% titanium dioxide, 1.2-1.6wt% cerium oxide, 2-4wt% sodium carbonate and 0.6-0.8wt% sodium nitrate.
[0018] As a preferred technical solution of the present invention, the expansion coefficient of the ceramic material is 2×10 -6 ~3.2×10 -6 K -1 , for example, it can be 2×10 -6 K -1 , 2.2×10 -6 K -1 , 2.4×10 -6 K -1 , 2.6×10 -6 K -1 , 2.8×10 -6 K -1 , 3×10 - 6 K -1 or 3.2 × 10 -6 K -1 , but not limited to the listed values, other values not listed within the numerical range are also applicable.
[0019] Preferably, the flexural strength of the ceramic material is 74-85 MPa, for example, 74 MPa, 76 MPa, 78 MPa, 80 MPa, 82 MPa or 85 MPa, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0020] Preferably, the temperature resistance of the ceramic material is 780-850°C, for example, it can be 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C or 850°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] In the present invention, the ceramic material has a lower expansion coefficient and higher bending strength, and can be cut or arranged in any shape to achieve fixation and installation inside a vacuum furnace; the ceramic material has a higher temperature resistance and can be used in a high-temperature environment for a long time, and its thermal conductivity is 1.3W / (m·K), which is similar to the thermal conductivity of a vacuum furnace (quartz furnace tube) of 1.4W / (m·K), and will not form stress concentration to reduce the life of the vacuum furnace.
[0022] As a preferred technical solution of the present invention, the purity of the quartz sand is ≥98.0wt%, for example, it can be 98wt%, 98.2wt%, 98.4wt%, 98.6wt%, 98.8wt% or 99wt%, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Preferably, the purity of the aluminum hydroxide, magnesium silicate, borax, lithium carbonate, titanium dioxide, cerium oxide, sodium carbonate and sodium nitrate is ≥99.5wt%, for example, it can be 99.5wt%, 99.6wt%, 99.7wt%, 99.8wt% or 99.9wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] In a second aspect, the present invention provides a method for preparing a ceramic material for an internal bracket of a vacuum furnace as provided in the first aspect, the preparation method comprising the following steps:
[0025] (1) Mixing raw materials according to a formula ratio, melting at high temperature, casting and annealing in sequence to obtain a glass plate;
[0026] (2) Mechanically treating and heat-treating the glass plate obtained in step (1) to obtain the ceramic material for the internal support of the vacuum furnace.
[0027] In the present invention, a glass plate is first prepared by high-temperature melting, casting and annealing, and then a glass plate of target size and shape is obtained by mechanical treatment. Finally, the glass plate is bent and ceramicized by heat treatment, and finally a ceramic material with performance and size that meet the requirements for making or assembling an internal bracket of a vacuum furnace is obtained.
[0028] As a preferred technical solution of the present invention, the temperature of the high temperature melting in step (1) is 1500-1700°C, for example, it can be 1500°C, 1550°C, 1600°C, 1650°C or 1700°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0029] Preferably, the high temperature melting time in step (1) is 3.5 to 4.5 h, for example, 3.5 h, 3.6 h, 3.7 h, 3.8 h, 3.9 h, 4.0 h, 4.1 h, 4.2 h, 4.3 h, 4.4 h or 4.5 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] Preferably, the annealing temperature in step (1) is 630-680°C, for example, it can be 630°C, 635°C, 640°C, 645°C, 650°C, 655°C, 660°C, 665°C, 670°C, 675°C or 680°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] It is worth noting that in the high-temperature melting process described in step (1) of the present invention, a suitable temperature (1500-1700°C) is used to ensure the complete melting of the prepared raw materials; a suitable melting temperature can ensure the complete melting of the mixed raw materials, and a suitable time can be used to ensure the uniformity of the glass components, while at the same time expelling bubbles and impurities in the melting process.
[0032] Appropriate annealing temperature can ensure the strength and appearance of the glass after forming;
[0033] Preferably, the annealing in step (1) further includes furnace cooling.
[0034] In the present invention, the purpose of annealing in step (1) is to eliminate the residual stress of the glass and ensure that the glass does not explode or its strength is reduced. In addition, the present invention limits the annealing temperature to ensure the strength and appearance of the glass after molding.
[0035] As a preferred technical solution of the present invention, the thickness of the glass plate in step (1) is 2.5 to 3 mm, for example, it can be 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm or 3 mm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0036] In the present invention, the thickness of the glass plate is 2.5-3 mm. If the thickness of the glass plate is too thick, the dimensional accuracy of the glass processing will be insufficient and the risk of cutting and cracking will increase. If the thickness of the glass plate is too thin, the strength of the glass will be reduced and it will be easy to break during processing.
[0037] As a preferred technical solution of the present invention, the mechanical processing in step (2) includes water jet cutting.
[0038] As a preferred technical solution of the present invention, the heat treatment in step (2) is carried out in a sintering furnace.
[0039] Preferably, the heat treatment in step (2) comprises: closing the door of the sintering furnace, heating up to a first temperature, a second temperature and a third temperature in sequence, keeping the temperature once and then opening the door of the sintering furnace to cool down to a fourth temperature, and then closing the door of the sintering furnace to keep the temperature twice and cool down with the furnace in sequence.
[0040] Preferably, the heating rate of the first temperature is 12 to 15°C / min, for example, it can be 12°C / min, 12.5°C / min, 13°C / min, 13.5°C / min, 14°C / min, 14.5°C / min or 15°C / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0041] Preferably, the first temperature is 750-850°C, for example, 750°C, 770°C, 790°C, 810°C, 830°C or 850°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0042] Preferably, the heating rate of the second temperature is 10 to 13°C / min, for example, it can be 10°C / min, 10.5°C / min, 11°C / min, 11.5°C / min, 12°C / min, 12.5°C / min or 13°C / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0043] Preferably, the second temperature is 1100-1150°C, for example, 1100°C, 1120°C, 1130°C, 1140°C or 1150°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0044] Preferably, the heating rate of the third temperature is 4 to 6°C / min, for example, it can be 4°C / min, 4.4°C / min, 4.8°C / min, 5.2°C / min, 5.6°C / min or 6°C / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0045] Preferably, the third temperature is 1200-1250°C, for example, it can be 1200°C, 1210°C, 1220°C, 1230°C, 1240°C or 1250°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0046] Preferably, the insulation time is 10 to 30 minutes, for example, 10 minutes, 14 minutes, 18 minutes, 22 minutes, 26 minutes or 30 minutes, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0047] Preferably, the cooling time is 3 to 10 minutes, for example, 3 minutes, 4 minutes, 6 minutes, 8 minutes or 10 minutes, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0048] Preferably, the fourth temperature is 900-950°C, for example, 900°C, 910°C, 920°C, 930°C, 940°C or 950°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0049] Preferably, the secondary insulation time is 1.8 to 2.5 h, for example, 1.8 h, 1.9 h, 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h or 2.5 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0050] It is worth noting that, during the heat treatment process described in the present invention, after the sintering furnace door is closed again, the heat treatment temperature will rebound, and the secondary insulation is carried out at the terminal temperature after the rebound; the terminal temperature after the rebound is 900-950°C, for example, it can be 900°C, 910°C, 920°C, 930°C, 940°C or 950°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0051] It is worth noting that the purpose of limiting multiple temperatures and different heating rates and holding times during the heat treatment process in step (2) of the present invention is to control the crystal growth rate and grain size in the microstructure, thereby controlling the physicochemical properties of the resulting ceramic material.
[0052] As a preferred technical solution of the present invention, the method for preparing a ceramic material for an internal bracket of a vacuum furnace provided in the second aspect of the present invention comprises the following steps:
[0053] (1) Mixing the raw materials according to the formula ratio, melting them at a temperature of 1500-1700° C. for 3.5-4.5 hours, annealing them at a temperature of 630-680° C. after casting, and cooling them in the furnace to obtain a glass plate with a thickness of 2.5-3 mm;
[0054] (2) subjecting the glass plate obtained in step (1) to post-mechanical treatment and heat treatment in a sintering furnace to obtain the ceramic material for the internal support of the vacuum furnace;
[0055] The heat treatment comprises: closing the door of the sintering furnace, heating the temperature to 750-850°C at a heating rate of 12-15°C / min, heating the temperature to 1100-1150°C at a heating rate of 10-13°C / min, and then heating the temperature to 1200-1250°C at a heating rate of 4-6°C / min, keeping the temperature for 10-30 minutes, opening the door of the sintering furnace, cooling the temperature to 900-950°C for 3-10 minutes, and then closing the door of the sintering furnace, keeping the temperature for 1.8-2.5 hours, and then cooling with the furnace.
[0056] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] (1) The ceramic material provided by the present invention has a low expansion coefficient, high bending strength and temperature resistance, and can be used in high temperature environments for a long time;
[0059] (2) The ceramic material provided by the present invention can be used to make the internal bracket of the vacuum furnace. Its thermal conductivity is similar to that of the vacuum furnace material (quartz tube), which avoids the stress concentration formed in the furnace body during the use of the vacuum furnace, thereby increasing the service life of the vacuum furnace;
[0060] (3) The ceramic material provided by the present invention is not easily oxidized and will not generate pollution sources when used in the internal support of a vacuum furnace, thereby maintaining the cleanliness of the vacuum environment inside the vacuum furnace and avoiding the influence of the vacuum furnace on the purity of the sintered sample. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is a DTA data analysis chart of the ceramic material provided in Example 1 of the present invention during the heat treatment process. DETAILED DESCRIPTION
[0062] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0063] Example 1
[0064] The present embodiment provides a ceramic material for an internal support of a vacuum furnace. The raw materials for preparing the ceramic material include, in terms of mass fraction: 33.97wt% quartz sand, 26.55wt% aluminum hydroxide, 17.06wt% magnesium silicate, 9.01wt% borax, 4.06wt% lithium carbonate, 4.13wt% titanium dioxide, 1.24wt% cerium oxide, 3.64wt% sodium carbonate and 0.34wt% sodium nitrate.
[0065] The purity of the quartz sand is 98.5wt%; the purity of the aluminum hydroxide, magnesium silicate, borax, lithium carbonate, titanium dioxide, cerium oxide, sodium carbonate and sodium nitrate are all 99.8wt%.
[0066] The method for preparing the ceramic material for the internal bracket of the vacuum furnace described in this embodiment comprises the following steps:
[0067] (1) Mixing the raw materials according to the formula ratio and melting them at 1600° C. for 3 hours to form a glass liquid without stones, bubbles or color lines, casting the molten glass liquid into a shape, annealing it at 650° C., and cooling it in the furnace to obtain a glass plate with a thickness of 2.75 mm;
[0068] (2) subjecting the glass plate obtained in step (1) to post-mechanical treatment and heat treatment in a sintering furnace to obtain the ceramic material for the internal support of the vacuum furnace;
[0069] The heat treatment includes: closing the sintering furnace door, heating to 800°C at a heating rate of 15°C / min, heating to 1150°C at a heating rate of 10°C / min, and then heating to 1220°C at a heating rate of 5°C / min, keeping warm for 20 minutes, opening the sintering furnace door, cooling for 6 minutes to 920°C, and then closing the sintering furnace door, keeping warm for 2 hours, and then cooling with the furnace.
[0070] The DTA data analysis diagram during the heat treatment process described in this embodiment is as follows Figure 1 As shown, according to Figure 1 It can be seen that during the heat treatment heating process of the glass plate obtained in step (1), the nucleation temperature of the material starts at 500°C and reaches a maximum value at 520°C; phase separation begins at 580°C to provide corresponding atoms for crystal growth; at around 650°C, phase separation is basically completed, and after continuously increasing the temperature, the kinetic energy of the atoms increases, gradually surrounding the crystal nucleus and starting to grow to form various types of solid solution materials such as quartz phase, pyroxene, spinel, etc.; at 920°C, the main crystal phase reaches the highest value, and the heat release also reaches the highest value; at 1200°C, the material softens and gradually enters the vitrification stage.
[0071] Example 2
[0072] The present embodiment provides a ceramic material for an internal support of a vacuum furnace. The raw materials for preparing the ceramic material include, in terms of mass fraction: 25wt% quartz sand, 30wt% aluminum hydroxide, 20wt% magnesium silicate, 6wt% borax, 5wt% lithium carbonate, 7.5wt% titanium dioxide, 1wt% cerium oxide, 5wt% sodium carbonate and 0.5wt% sodium nitrate.
[0073] The purity of the quartz sand is 98.2wt%; the purity of the aluminum hydroxide, magnesium silicate, borax, lithium carbonate, titanium dioxide, cerium oxide, sodium carbonate and sodium nitrate are all 99.5wt%.
[0074] The method for preparing the ceramic material for the internal bracket of the vacuum furnace described in this embodiment comprises the following steps:
[0075] (1) Mixing the raw materials according to the formula ratio, melting them at 1500° C. for 4.5 hours, annealing them at 630° C. after casting, and cooling them in the furnace to obtain a glass plate with a thickness of 2.5 mm;
[0076] (2) subjecting the glass plate obtained in step (1) to post-mechanical treatment and heat treatment in a sintering furnace to obtain the ceramic material for the internal support of the vacuum furnace;
[0077] The heat treatment includes: closing the sintering furnace door, heating to 750°C at a heating rate of 12°C / min, heating to 1100°C at a heating rate of 11.5°C / min, and then heating to 1200°C at a heating rate of 4°C / min, keeping warm for 30 minutes, opening the sintering furnace door, cooling to 900°C for 10 minutes, and then closing the sintering furnace door, keeping warm for 2.5 hours, and then cooling with the furnace.
[0078] Example 3
[0079] The present embodiment provides a ceramic material for an internal support of a vacuum furnace. The raw materials for preparing the ceramic material include, in terms of mass fraction: 40wt% quartz sand, 25wt% aluminum hydroxide, 12wt% magnesium silicate, 12wt% borax, 2wt% lithium carbonate, 5wt% titanium dioxide, 2wt% cerium oxide, 1wt% sodium carbonate and 1wt% sodium nitrate.
[0080] The purity of the quartz sand is 98.0wt%; the purity of the aluminum hydroxide, magnesium silicate, borax, lithium carbonate, titanium dioxide, cerium oxide, sodium carbonate and sodium nitrate are all 99.7wt%.
[0081] The method for preparing the ceramic material for the internal bracket of the vacuum furnace described in this embodiment comprises the following steps:
[0082] (1) Mixing the raw materials according to the formula ratio, melting them at 1700° C. for 3.5 hours, annealing them at 680° C. after casting, and cooling them in the furnace to obtain a glass plate with a thickness of 3 mm;
[0083] (2) subjecting the glass plate obtained in step (1) to post-mechanical treatment and heat treatment in a sintering furnace to obtain the ceramic material for the internal support of the vacuum furnace;
[0084] The heat treatment includes: closing the sintering furnace door, heating to 850°C at a heating rate of 13.5°C / min, heating to 1150°C at a heating rate of 13°C / min, and then heating to 1250°C at a heating rate of 6°C / min, keeping warm for 10 minutes, opening the sintering furnace door, cooling for 10 minutes to 950°C, and then closing the sintering furnace door, keeping warm for 1.8 hours, and then cooling with the furnace.
[0085] Example 4
[0086] This embodiment provides a ceramic material for an internal support of a vacuum furnace. The raw materials for preparing the ceramic material are the same as those in Embodiment 1.
[0087] The method for preparing the ceramic material for the internal support of the vacuum furnace described in this embodiment is different from that in Embodiment 1 only in that:
[0088] In this embodiment, the heat treatment in step (2) is adjusted as follows: close the sintering furnace door, heat up to 1220°C at a heating rate of 10°C / min, keep warm for 20 minutes, open the sintering furnace door and cool down to 920°C, then close the sintering furnace door and keep warm for 2 hours before cooling with the furnace.
[0089] Example 5
[0090] This embodiment provides a ceramic material for an internal support of a vacuum furnace. The raw materials for preparing the ceramic material are the same as those in Embodiment 1.
[0091] The method for preparing the ceramic material for the internal support of the vacuum furnace described in this embodiment is different from that in Embodiment 1 only in that:
[0092] In this embodiment, the heat treatment in step (2) is adjusted as follows: close the sintering furnace door, heat up to 800°C at a heating rate of 15°C / min, heat up to 1150°C at a heating rate of 10°C / min, keep warm for 20 minutes, open the sintering furnace door and cool down to 920°C for 6 minutes, then close the sintering furnace door and keep warm for 2 hours before cooling with the furnace; that is, the process of heating to the third temperature is omitted in this embodiment.
[0093] Example 6
[0094] This embodiment provides a ceramic material for an internal support of a vacuum furnace. The raw materials for preparing the ceramic material are the same as those in Embodiment 1.
[0095] The method for preparing the ceramic material for the internal support of the vacuum furnace described in this embodiment is different from that in Embodiment 1 only in that:
[0096] In this embodiment, one heat preservation process in the heat treatment process described in step (2) is omitted.
[0097] Example 7
[0098] This embodiment provides a ceramic material for an internal support of a vacuum furnace. The raw materials for preparing the ceramic material are the same as those in Embodiment 1.
[0099] The method for preparing the ceramic material for the internal support of the vacuum furnace described in this embodiment is different from that in Embodiment 1 only in that:
[0100] In this embodiment, the first insulation process in the heat treatment process of step (2) is omitted, and the second insulation time is adjusted to 1 hour.
[0101] Example 8
[0102] This embodiment provides a ceramic material for an internal support of a vacuum furnace. The raw materials for preparing the ceramic material are the same as those in Embodiment 1.
[0103] The method for preparing the ceramic material for the internal support of the vacuum furnace described in this embodiment is different from that in Embodiment 1 only in that:
[0104] In this embodiment, the secondary insulation time in the heat treatment process of step (2) is adjusted to 1 hour.
[0105] Comparative Example 1
[0106] This comparative example provides a ceramic material for an internal bracket of a vacuum furnace. The raw materials for preparing the ceramic material differ from those in Example 1 only in that:
[0107] In this embodiment, the content of lithium carbonate in the preparation raw material is adjusted to 6.1wt%, and the content of titanium dioxide is adjusted to 2.09wt%.
[0108] The preparation method of the ceramic material for the internal support of the vacuum furnace described in this embodiment is the same as that in Example 1.
[0109] Comparative Example 2
[0110] This comparative example provides a ceramic material for an internal bracket of a vacuum furnace. The raw materials for preparing the ceramic material differ from those in Example 1 only in that:
[0111] In this embodiment, the content of lithium carbonate in the preparation raw material is adjusted to 1.8 wt %, and the content of titanium dioxide is adjusted to 6.39 wt %.
[0112] The preparation method of the ceramic material for the internal support of the vacuum furnace described in this embodiment is the same as that in Example 1.
[0113] Comparative Example 3
[0114] This comparative example provides a ceramic material for an internal bracket of a vacuum furnace. The raw materials for preparing the ceramic material differ from those in Example 1 only in that:
[0115] In this embodiment, the content of quartz sand in the preparation raw material is adjusted to 30wt%, and the content of aluminum hydroxide is adjusted to 31.52wt%.
[0116] The preparation method of the ceramic material for the internal support of the vacuum furnace described in this embodiment is the same as that in Example 1.
[0117] Comparative Example 4
[0118] This comparative example provides a ceramic material for an internal bracket of a vacuum furnace. The raw materials for preparing the ceramic material differ from those in Example 1 only in that:
[0119] In this embodiment, the content of quartz sand in the preparation raw material is adjusted to 20wt%, and the content of aluminum hydroxide is adjusted to 40.52wt%.
[0120] The preparation method of the ceramic material for the internal support of the vacuum furnace described in this embodiment is the same as that in Example 1.
[0121] Performance testing:
[0122] (1) According to the provisions of GB / T16920-1997, the thermal expansion coefficient of the ceramic materials provided in the above embodiments and comparative examples was tested using an Orton 2012STD thermal expansion instrument, and the results are shown in Table 1;
[0123] (2) According to the provisions of GB / T 37781-2019, the bending strength test of the ceramic materials provided in the above embodiments and comparative examples was carried out using a HDW-20 universal testing machine, and the results are shown in Table 1;
[0124] (3) The temperature resistance of the ceramic materials provided in the above embodiments and comparative examples was tested using a KSL-1200X muffle furnace. The results are shown in Table 1.
[0125] The temperature resistance test standard is: if the tested ceramic material does not deform after being kept at a certain temperature for 6 hours, it means that the ceramic material has excellent temperature resistance at this temperature;
[0126] (4) A KSL-1200X muffle furnace was used to perform a thermal shock resistance test on the ceramic materials provided in the above embodiments and comparative examples. The results are shown in Table 1.
[0127] The thermal shock resistance test standard is: at a test temperature of 600°C, the ceramic material to be tested is impacted repeatedly for 5 times, and it is considered excellent if no cracking sound is heard.
[0128] Table 1
[0129]
[0130] According to Table 1, we can know the following points:
[0131] (1) Comprehensive analysis of Examples 1-3 shows that the ceramic material provided by the present invention has a low thermal expansion coefficient, excellent bending strength, temperature resistance and thermal shock resistance, so that the obtained ceramic material can be used to make the internal bracket of the vacuum furnace, and will not affect the service life of the vacuum furnace during the operation of the vacuum furnace, nor will it cause pollution to the sample in the vacuum furnace;
[0132] (2) Comprehensive analysis of Example 1 and Examples 4-8 shows that the heat treatment process will affect the thermal expansion coefficient, bending strength, temperature resistance and thermal shock resistance of the ceramic material;
[0133] When the temperature is directly raised to the target temperature (1220°C) at a heating rate of 10°C / min, the material will be deformed and lose its processing value;
[0134] When the final temperature is adjusted to 1150° C. (as in Example 5), the material will form a rough fracture morphology and will not be resistant to thermal shock testing;
[0135] When the first heat preservation process is omitted and / or the second heat preservation time is shortened, the expansion coefficient of the obtained ceramic material increases, and the bending strength, temperature resistance and heat shock resistance are all reduced, so that when the ceramic material is used for the internal bracket of the vacuum furnace, its service life is reduced;
[0136] (3) Comprehensive analysis of Example 1 and Comparative Examples 1-4 shows that the silicon-to-aluminum ratio, the content of lithium carbonate and titanium dioxide in the raw materials for preparing the ceramic material will affect the thermal expansion coefficient, flexural strength, temperature resistance and thermal shock resistance of the ceramic material;
[0137] When the content of lithium carbonate is too high (the content of titanium dioxide is too low), or the content of lithium carbonate is too low (the content of titanium dioxide is too high), the expansion coefficient of the obtained porcelain material will increase, and the bending strength, temperature resistance and thermal shock resistance will all decrease;
[0138] When the content of aluminum hydroxide is too high (such as in Comparative Example 3), the temperature resistance of the material will increase, the thermal expansion coefficient will increase, and it will not be resistant to thermal shock test;
[0139] When the content of quartz sand is too high (such as comparative example 4), the crystal content of the material will be reduced, the expansion coefficient will be increased, and it will not be resistant to thermal shock test.
[0140] In summary, the ceramic material provided by the present invention is used to prepare a bracket for use inside a vacuum furnace, which can effectively increase the life of the vacuum furnace, avoid damage to the vacuum furnace caused by the internal bracket during installation or use, and also increase the service life of the internal bracket.
[0141] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A ceramic material for an internal support of a vacuum furnace, characterized in that: Measured in percentage by mass, the raw materials for preparing the ceramic material include: 25-40wt% quartz sand, 20-30wt% aluminum hydroxide, 12-20wt% magnesium silicate, 6-12wt% borax, 2-5wt% lithium carbonate, 2-8wt% titanium dioxide, 1-2wt% cerium oxide, 1-5wt% sodium carbonate and 0.2-1.0wt% sodium nitrate.
2. The ceramic material for the internal support of a vacuum furnace according to claim 1, characterized in that: Measured in percentage by mass, the raw materials for preparing the ceramic material include: 30-35wt% of quartz sand, 20-25wt% of aluminum hydroxide, 15-18wt% of magnesium silicate, 8-10wt% of borax, 3.5-4.5wt% of lithium carbonate, 4-6wt% of titanium dioxide, 1.2-1.6wt% of cerium oxide, 2-4wt% of sodium carbonate and 0.6-0.8wt% of sodium nitrate.
3. The ceramic material for the internal support of a vacuum furnace according to claim 1 or 2, characterized in that: The expansion coefficient of the ceramic material is 2×10 -6 ~3.2×10 -6 K -1 ; Preferably, the flexural strength of the ceramic material is 74-85 MPa; Preferably, the temperature resistance of the ceramic material is 780-850°C.
4. The ceramic material for the internal support of a vacuum furnace according to any one of claims 1 to 3, characterized in that: The purity of the quartz sand is ≥98.0wt%; Preferably, the purity of the aluminum hydroxide, magnesium silicate, borax, lithium carbonate, titanium dioxide, cerium oxide, sodium carbonate and sodium nitrate is ≥99.5wt%.
5. A method for preparing a ceramic material for an internal support of a vacuum furnace as claimed in any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) Mixing raw materials according to a formula ratio, melting at high temperature, casting and annealing in sequence to obtain a glass plate; (2) Mechanically treating and heat-treating the glass plate obtained in step (1) to obtain the ceramic material for the internal support of the vacuum furnace.
6. The preparation method according to claim 5, characterized in that: The high temperature melting temperature of step (1) is 1500-1700° C. Preferably, the high temperature melting time in step (1) is 3.5 to 4.5 hours; Preferably, the annealing in step (1) is performed at a temperature of 630 to 680° C. Preferably, the annealing in step (1) further includes furnace cooling.
7. The preparation method according to claim 5 or 6, characterized in that: The thickness of the glass plate in step (1) is 2.5 to 3 mm.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The mechanical processing in step (2) includes water jet cutting.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The heat treatment in step (2) is carried out in a sintering furnace; Preferably, the heat treatment in step (2) comprises: closing the door of the sintering furnace, heating up to a first temperature, a second temperature and a third temperature in sequence, keeping the temperature once, opening the door of the sintering furnace and cooling down to a fourth temperature, and then closing the door of the sintering furnace and keeping the temperature twice and cooling with the furnace in sequence; Preferably, the heating rate of the first temperature is 12-15°C / min; Preferably, the first temperature is 750-850°C; Preferably, the heating rate of the second temperature is 10-13°C / min; Preferably, the second temperature is 1100-1150°C; Preferably, the heating rate of the third temperature is 4-6°C / min; Preferably, the third temperature is 1200-1250°C; Preferably, the time of the first insulation is 10 to 30 minutes; Preferably, the cooling time is 3 to 10 minutes; Preferably, the fourth temperature is 900-950°C; Preferably, the secondary insulation time is 1.8 to 2.5 hours.
10. The preparation method according to any one of claims 5 to 9, characterized in that: The preparation method comprises the following steps: (1) Mixing the raw materials according to the formula ratio, melting them at a temperature of 1500-1700° C. for 3.5-4.5 hours, annealing them at a temperature of 630-680° C. after casting, and cooling them in the furnace to obtain a glass plate with a thickness of 2.5-3 mm; (2) subjecting the glass plate obtained in step (1) to post-mechanical treatment and heat treatment in a sintering furnace to obtain the ceramic material for the internal support of the vacuum furnace; The heat treatment comprises: closing the door of the sintering furnace, heating the temperature to 750-850°C at a heating rate of 12-15°C / min, heating the temperature to 1100-1150°C at a heating rate of 10-13°C / min, and then heating the temperature to 1200-1250°C at a heating rate of 4-6°C / min, keeping the temperature for 10-30 minutes, opening the door of the sintering furnace, cooling the temperature to 900-950°C for 3-10 minutes, and then closing the door of the sintering furnace, keeping the temperature for 1.8-2.5 hours, and then cooling with the furnace.